Element geochemistry, mineralogy, geochronology and zircon Hf isotope of the Luxi and Xiazhuang granites in Guangdong province, China: Implications for U mineralization - Chen, You-Wei; Bi, Xian-Wu; Hu, Rui-Zhong; Dong, Shao-Hua (Lithos, 2012)
The Luxi and Xiazhuang granitic plutons are parts of the Guidong granite belt in northern Guangdong Province, China. They occur next to each other and have similar crystallization ages. However, the Xiazhuang pluton hosts several important uranium (U) ore deposits, whereas the Luxi pluton does not. This study compares the two plutons using whole-rock geochemistry, biotite compositions, zircon U–Pb ages by LA-ICPMS, and in situ zircon Hf isotope data by LA-MC-ICPMS, to understand the fundamental controls. Results show that the two plutons have similar ages, 237Ma for the Luxi pluton and 234Ma for the Xiazhuang pluton. They also have similar geochemical features that are characteristic of S-type granites. Zircons from both plutons have negative εHf(t) values (−9 to −12) and a Paleoproterozoic two-stage Hf model age (TDM2=1838Ma to 2025Ma), suggesting that their parental magmas were all derived from Paleoproterozoic metasedimentary rocks. The geochemical and petrological data suggest that these two plutons crystallized from magmas derived from the same parent at different stages, the parental magma of the Xiazhuang pluton is more evolved than that of the Luxi pluton. This factor, plus different physical–chemical conditions (such as temperature, volatile components and oxidation state) resulted in higher U content and favorable U-bearing species in the Xiazhuang magmatic hydrothermal system. U occurs mainly as uraninite in the Xiazhuang pluton, which facilitates U transfer from granite into CO2-rich hydrothermal fluid to form U ore deposits. In contrast, U occurs mainly as REE-bearing minerals in the Luxi magmatic system, preventing U transfer to associated hydrothermal fluids. As a result, the Xiazhuang pluton hosts several important uranium ore deposits, whereas the Luxi pluton is ore-barren. ► The zircon U–Pb age and Hf isotope of the biotite granite and two-mica granite are investigated. ► We ascertain the evolution relation between the two granites. ► F content and physic-chemical conditions control the form of uranium in granites. ► The potential of uranium mineralization is controlled by form of uranium in granites.